Fidelity, stances, and explaining cultural stability. (10th November 2022) - Buskell, Andrew; Charbonneau, Mathieu
Abstract: The bifocal stance theory posits two stances – the ritual and the instrumental – each a learning strategy with different fidelity outcomes. These differences in turn have long-term consequences for cultural stability. Yet we suggest the key concept of "fidelity" is insufficiently explicated. Pointing to counterexamples and gaps in the theory, we suggest that explicating "fidelity" reveals the stances to be heuristic explanatory strategies : first-pass explanatory glosses of learning and its consequences, not descriptions of the inner machinery of agents.